Facilitating reflection: a review and synthesis of the factors enabling effective facilitation of reflective practice. Issue 4 (4th July 2022) - Marshall, T.; Keville, S.; Cain, A.; Adler, J. R.
ABSTRACT: Reflective practice is an inherently personal and relational process, occurring privately within people, and publicly, between people. Consequently, given it positively impacts on professional practice, it has become a personal and professional requirement for professional bodies accrediting practitioners. This literature synthesis aims to consolidate understanding around the factors facilitating reflection by generating insights from a variety of publications across professional contexts. The analytical process involved initial coding and focussed coding wherein article text was fragmented, sorted, and integrated to develop a thematic structure. Analysis resulted in two higher order themes: Factors facilitating reflection; and Facilitator tasks. Results highlighted the value of supportive environments to facilitate open enquiry alongside focussed formal dialogues between peers, more experienced colleagues, and formal facilitators to enrich knowledge, perspectives, insights, and relationships. Further, to begin the reflective process, practitioners and novice learners benefit from support in deconstructing the concept of reflection. Ideally, this would be facilitated by an experienced reflective facilitator who values an open enquiry towards complexity, difference, and emotive responses. This requires safe, supportive, and blame-free environments where facilitators encourage dialogue while modelling qualities such as congruence, acceptance, and empathy.